Age Considerations in Four-Corner Arthrodesis and Proximal Row Carpectomy: A Review - Heifner, John J.; Karadimas, Thomas; DeVito, Paul M.; Gomez, Osmanny; Kolovich, Gregory P. (Journal of Wrist Surgery, 2023)
Purpose Although indications for four-corner arthrodesis (4CA) and proximal row carpectomy (PRC) are not completely aligned, the surgeon is often tasked with deciding between these options which vary in the surgical technique and complication profile. Patient age is often discussed as a determining factor for treatment; however, outcome data for these procedures are rarely stratified by patient age. Our objective was to perform a systematic review on the age-specific outcomes for 4CA and PRC.Materials and Methods A PubMed database search for 4CA and PRC was performed according to Preferred Reporting Items for Systematic Reviews and Meta-analysis guidelines. The inclusion criteria required individual case reporting of patient age, surgical intervention, and appropriate outcome measures. The data were stratified by procedure and by patients older and younger than 45 years.Results Within the 4CA group, the relative risk for a disabilities of the arm, shoulder, and hand (DASH) score above 30 was 1.94 (95% confidence interval, 1.1–3.67) in patients over 45 years compared with patients under 45 years. Within the PRC group, grip strength as a percentage of the contralateral side was higher in the over 45 age group (mean 75%) compared to the under 45 age group (mean 61%) but did not reach the level of significance.Conclusion Despite satisfactory results for 4CA in aggregate, the distribution of scores indicates the need for setting expectations when treating younger adult patients with 4CA. The current results demonstrate increased disability based on DASH score following 4CA in patients under 45 years compared with patients over 45 years. Although outcomes were comparable between younger and older adults following PRC, recovery of grip strength may occur less frequently in younger adults.Level of evidence IV systematic review.
Keywords: four corner fusion; proximal row carpectomy; SLAC; SNAC; wrist arthritis